On the Measurement of Consumer Preferences and Food Choice Behavior: The Relation Between Visual Attention and Choices. (10th October 2018) - Van Loo, Ellen J; Grebitus, Carola; Nayga, Rodolfo M; Verbeke, Wim; Roosen, Jutta
Abstract: When buying a product, consumers are confronted with a host of information presented to them. However, this information can only affect shoppers' choices if they pay attention to it. Eye tracking can measure visual attention to information. Most recently, agricultural and food economics research has combined eye tracking and valuation methods to give insight into the relation between visual attention, preferences, and choices. We present an overview of the eye‐tracking literature, and discuss theory and applications. Also, insights on how to measure visual attention and choice are provided. While eye tracking has its challenges, there are interesting future research avenues that can be explored by agricultural and food economists using eye tracking.